2016
DOI: 10.1248/bpb.b16-00421
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Kampo Formula “Juzen-taiho-to” on Carbon Tetrachloride-Induced Hepatotoxicity in Mice

Abstract: The aim of the present study was to investigate whether pretreatment with the Japanese herbal medicine, "Juzen-taiho-to" (JTX), had an ameliorative effect on carbon tetrachloride (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Moreover, i.p. administration of JTX induces an increase in hepatic MT (Yoshioka et al, 2016a). Our results showed that administration of JTX did not increase in the hepatic MT levels, which suggests that MT does not involve a protective role in the present investigation.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Moreover, i.p. administration of JTX induces an increase in hepatic MT (Yoshioka et al, 2016a). Our results showed that administration of JTX did not increase in the hepatic MT levels, which suggests that MT does not involve a protective role in the present investigation.…”
Section: Discussionsupporting
confidence: 42%
“…We measured the plasma levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) using the Transaminase CII Test Wako (Wako Pure Chemical, Osaka, Japan) according to the manufacturer's instructions and as previously described (Yoshioka et al, 2016a).…”
Section: Biochemical Analysis Of Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Total malondialdehyde (MDA) levels were estimated by a colorimetric microplate assay (Oxford Biochemical Research, Oxford, MI, USA) according to the manufacturer's protocol and as previously described (Yoshioka et al, 2016a(Yoshioka et al, , 2016b.…”
Section: Measurement Of Malondialdehyde Levels and Total Antioxidant mentioning
confidence: 99%
“…The levels of these enzymes provide a sensitive diagnostic for liver damage (Kim et al, ). Similarly, increased serum AKP is associated with the liver cell membrane injury (Yoshioka et al, ). Increased serum γ‐GT can result in the production of free radicals (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%